A Case report - On-pump Coronary Artery Bypass in a Paraplegic Patient - Derriks, Xavier Antonio Bohorquez; Dincq, Anne-Sophie; Kalscheuer, Grégory; Michaux, Isabelle; Mitchell, John; Melly, Ludovic (Cardiology and Cardiovascular Medicine, 2019)
Here, we report a 71-year-old Caucasian male with a chronic spinal cord injury at the level of T4, who underwent a coronary artery bypass grafting for a 3-vessel disease. During surgery an almost fatal hypotension took place in the presence of an autonomic dysregulation, requiring to go back on cardiopulmonary bypass. A few other episodes of hyper- and hypotension occurred perioperatively. We discuss the issues with the anesthesia and surgical cardiac procedures in the light of this acute blood pressure variability called autonomic dysreflexia.